USING VIDEO MATERIALS IN DEVELOPING COMMUNICATIVE COMPETENCE OF STUDENTS (Scientific journal of the Fergana State University, 2023)
The use of video in the classroom is very effective in the formation of communicative competence of students. The purpose of the study is to analyse the issues of using authentic video materials in developing students’ communicative competence. The methods of scientific research as analysis, synthesis, deduction and other theoretical research methods were applied. Results. The research work comprises the developing students’ communicative competence (speaking skills and listening skills) through watching authentic films. Conclusion. Using video material facilitates for developing of learning process. It will be helpful in formation of professional competence of future specialists.